Unraveling the Mystery of Exozodiacal Dust. Issue Volume 8:Issue S299(2013) (6th January 2014) - Ertel, S.; Augereau, J.-C.; Thébault, P.; Absil, O.; Bonsor, A.; Defrère, D.; Kral, Q.; Le Bouquin, J.-B.; Lebreton, J.; Coudé du Foresto, V.
Abstract: Exozodiacal dust clouds are thought to be the extrasolar analogs of the Solar System's zodiacal dust. Studying these systems provides insights in the architecture of the innermost regions of planetary systems, including the Habitable Zone. Furthermore, the mere presence of the dust may result in major obstacles for direct imaging of earth-like planets. Our EXOZODI project aims to detect and study exozodiacal dust and to explain its origin. We are carrying out the first large, near-infrared interferometric survey in the northern ( CHARA /FLUOR) and southern ( VLTI /PIONIER) hemispheres. Preliminary results suggest a detection rate of up to 30% around A to K type stars and interesting trends with spectral type and age. We focus here on presenting the observational work carried out by our team.